2022
DOI: 10.1371/journal.pone.0277174
|View full text |Cite
|
Sign up to set email alerts
|

The psychological distress and suicide-related ideation in hospital workers during the COVID-19 pandemic: Second results from repeated cross-sectional surveys

Abstract: The COVID-19 pandemic has been affecting the mental health of hospital workers. During the prolonged pandemic, hospital workers may experience much more severe psychological distress, leading to an increased risk of suicide. This study aimed to investigate changes in psychological effects on hospital workers over 12 months from the beginning of the pandemic and clarify factors associated with psychological distress and suicide-related ideation 1-year after the pandemic’s beginning. These repeated, cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Moreover, fear of COVID-19 was associated with intolerance of uncertainty ( 41 ) and social isolation during the COVID-19 pandemic ( 42 ). Therefore, our results do not contradict those of the aforementioned studies; rather, given that severe general and event-related distress were a risk factor for suicidal ideation in Ide et al’s study ( 7 ), the importance of fear of COVID-19 in the mental health of HCWs highlighted in the present study becomes more prominent.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Moreover, fear of COVID-19 was associated with intolerance of uncertainty ( 41 ) and social isolation during the COVID-19 pandemic ( 42 ). Therefore, our results do not contradict those of the aforementioned studies; rather, given that severe general and event-related distress were a risk factor for suicidal ideation in Ide et al’s study ( 7 ), the importance of fear of COVID-19 in the mental health of HCWs highlighted in the present study becomes more prominent.…”
Section: Discussionsupporting
confidence: 55%
“…The present study focused on psychological distress as measured by K6; however, in addition to general distress, Ide et al ( 7 ) examined event-related distress and found that general and event-related distress were associated with isolation and exhaustion, while event-related distress was also associated with uncertainty. Moreover, fear of COVID-19 was associated with intolerance of uncertainty ( 41 ) and social isolation during the COVID-19 pandemic ( 42 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Given that patients with SA also experience SI, the similarly high level of psychological stress symptoms would suggest that it is related to the development of suicidal thoughts rather than behavior. In support, population surveys indicate that psychological distress is a strong correlate of SI both in the pandemic (57,58) as well as in the pre-pandemic period (59). In addition, current theories emphasize that clinical risk factors for suicidal ideation and suicidal acts partly overlap, but also have some unique features (60)(61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%